Multiple-System Atrophy in Long-Term Professional Painter: A Case Report. (19th June 2012) - Nagai, Yusa; Kitazawa, Riko; Nakagawa, Miku; Komoda, Munenori; Kondo, Takeshi; Haraguchi, Ryuma; Kitazawa, Sohei
Abstract : Introduction . Multiple system atrophy (MSA) is a rare and severe adult-onset, sporadic, and progressive neurodegenerative disorder. Here, we describe an autopsy case of MSA in a long-term professional painter. Although typical glial cytoplasmic inclusion (GCI) was not observed in a routine histological examination, strong α-synuclein immunostaining in the nucleus confirmed the diagnosis of MSA. Case Presentation . A 48-year-old Japanese man with a long occupational history of professional painter was sent to the emergency room, where he died of multiple organ failure. The patient had suffered tremors and inarticulateness at age 28, developed diabetes at 42 and was diagnosed with spinocerebellar degeneration at 46. A histopathological examination showed severe neuronal loss, gliosis, and tissue rarefaction in the paleostriatum, striate body of the substantia nigra, the pons, and the olivary nucleus of the upper medulla oblongata, intermediolateral of the spinal gray matter (sacral region). α-synuclein-positive GCI in oligodendroglia was occurred in the cerebral cortex, the midbrain, the medulla oblongata, and the spinal cord. These findings confirmed the presence of multiple-system atrophy (OPCA+ SDS). Conclusion . Although the pathogenesis of MSA is still unclear, prolonged, and extensive exposure to organic solvents, together with a hyperglycemic morbidity attributed to diabetes, may have contributed to the onset and clinical course of the present case.